Estimation of Carbon Stocks in Mangrove Ecosystems as Blue Carbon Mitigation on the South Coast of Lombok Island - Pahmi Husain; Muhammad Shohibul Ihsan (Jurnal Penelitian Pendidikan IPA, 2026)
Mangrove ecosystems are globally recognized as major blue carbon sinks, yet site-specific evidence linking sediment carbon, nutrient availability, and community structure in sandy mangrove substrates remains limited, particularly along the south coast of Lombok Island. This study addresses that gap by examining how sediment carbon content relates to mangrove diversity, substrate texture, and nutrients across three stations namely Tanjung Luar, Kedome, and Poton Bako. A field survey using systematic line transects (10×10 m trees; 5×5 m saplings; 2×2 m seedlings) was combined with sediment coring (0–100 cm). Sediment carbon was measured by Loss on Ignition (LOI), while texture and nutrients (N, P, K) were analyzed in the laboratory. Mangrove communities showed moderate diversity (H' = 0.45–1.50). Poton Bako exhibited the highest diversity and evenness (H' = 1.50; E = 0.87), indicating a relatively stable stand compared with Tanjung Luar and Kedome. Sediment carbon varied by location and species, with the highest values associated with Rhizophora apiculata, Rhizophora mucronata, and Sonneratia alba, reaching up to 875.22, 825.45, and 665.55, respectively. Although sediments were predominantly sandy (>50%), finer fractions (silt-clay, ±5-47%) and relatively high nutrients in Rhizophora zones (N up to 4.28%; P up to 99.35 ppm; K up to 22.63 meq%) enhanced carbon retention. Environmental parameters were within optimal ranges (pH 5.7-6.2; salinity 34.5–35.5‰; temperature 27-29°C). These findings indicate that even sandy mangrove substrates can store substantial carbon when supported by favorable nutrient conditions and stable species composition, highlighting the blue carbon significance of South Lombok mangroves for ecosystem-based coastal management. Limitations include reliance on LOI for carbon estimation and the absence of seasonal measurements, which may influence carbon and nutrient dynamics.